Manganese-doped aluminum-rich magnesium aluminate spinel transparent ceramic phosphor and preparation method thereof
By using manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic materials, the problems of insufficient green light emission, poor thermal stability and short service life of existing WLED backlight sources are solved, and green fluorescent transparent ceramic materials with high optical quality and high thermal stability are achieved, improving the stability and application fields of LED devices.
Patent Information
- Application Number
- CN202411878458.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The backlight source of the existing white light emitting diode (WLED) has problems such as insufficient green light emission, poor thermal stability and short service life due to the use of YAG:Ce3+ yellow phosphor, and poor thermal conductivity and low chemical stability of the organic resin, resulting in a decrease in the LED luminescence intensity and chromaticity shift.
Manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor material was used to prepare Mg1-x-yAl2+2x/3O4:yMn single-phase ceramic powder through high-temperature solid phase reaction, and dry press molding, pressure-free pre-sintering and thermal isostatic sintering were carried out to optimize the process to improve optical quality and thermal stability.
Green fluorescent transparent ceramic materials with high optical quality, narrow half-maximum wide emission, high thermal stability and high thermal conductivity have been achieved, which solves the problems of low color gamut, poor thermal stability and short service life of traditional WLED backlight sources, and improves the stability and application fields of LED devices.
Smart Images

Figure HDA0005197547660000011 
Figure HDA0005197547660000012 
Figure HDA0005197547660000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of transparent ceramic photofunctionalization, and specifically relates to a manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor and a preparation method thereof. Background Art
[0002] White light emitting diodes (WLEDs) have long been used as the backlight source for typical liquid crystal displays (LCDs) due to their advantages such as energy saving, long life, environmental protection and low cost. Currently, the mainstream commercial white light illumination and LCD backlight source is a combination of blue InGaN chips and YAG:Ce 3+ Yellow phosphor is combined to mix the right amount of blue light with yellow light to obtain white light, however, YAG:Ce 3+ The half-peak width is wide, the green light emission is insufficient, the thermal stability is poor, the heat generation is serious, the service life is short and the color gamut of the backlight is relatively low.
[0003] In order to meet the requirements of backlight technology, various green or red luminescent materials have been developed. Phosphors usually require organic resins or silicone resins to be coated on the surface of the chip. Due to the poor thermal conductivity and low chemical stability of organic resins, they are prone to aging and yellowing, which eventually leads to a decrease in LED luminous intensity and chromaticity shift. The development of transparent ceramic phosphors that do not use organic resins can effectively solve these problems. Summary of the invention
[0004] The main purpose of the present invention is to provide a manganese-doped aluminum-rich magnesium-aluminum spinel green transparent ceramic phosphor material with high optical quality, narrow half-peak emission width, high thermal stability and high thermal conductivity in response to the problems and shortcomings of the prior art.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor, which is a single-phase magnesium-aluminum spinel structure with a stoichiometric formula of Mg 1-x-y Al 2+2x / 3 O4:yMn, its 0 <x≤0.25;0.004≤y≤0.1。
[0007] Furthermore, the manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor introduces more cation defects, increases lattice distortion, reduces the symmetry of the lattice, causes the symmetrical lattice sites to deviate from the inversion center, and relaxes the Mn 2+ The degree of parity forbidden transition of Mn 2+ of direct excitation and emission intensities.
[0008] In the above scheme, the manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor has a block structure and a thickness of 2 to 8 mm, preferably 2 to 3 mm.
[0009] In the above solution, the manganese-doped aluminum-rich magnesium aluminate spinel transparent ceramic phosphor has green fluorescence, an internal quantum efficiency of 73-96%, and a transmittance of more than 78% at 800 nm.
[0010] The preparation method of the above-mentioned manganese-doped aluminum-rich magnesium aluminate spinel transparent ceramic phosphor includes the following steps: First, Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder is prepared by high-temperature solid-state reaction, and then dry pressing and pressureless pre-sintering are carried out to obtain a ceramic sintered body with closed pores and high density. Then, the ceramic pre-sintered body is subjected to hot isostatic pressing treatment.
[0011] Further, the preparation method of the Mn 2+ ion-doped aluminum-rich magnesium aluminate fluorescent transparent ceramic specifically includes the following steps:
[0012] 1) Raw material weighing: Using MgO, Al2O3, and MnCO3 as raw materials, they are proportioned according to the molar ratio of 1-x-y:(1+x / 3):y, where 0<x≤0.25; 0.004≤x≤0.1; ball milling and mixing, and sieving;
[0013] 2) Synthesis of Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder: The mixed powder obtained in step 1) is subjected to high-temperature solid-state reaction to obtain Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase compound, ball milling and sieving to obtain Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder;
[0014] 3) Dry pressing: The powder obtained in step 2) is dry pressed to obtain a green body, and then cold isostatic pressing treatment is carried out;
[0015] 4) Pre-sintering: The green body obtained in step 5) is pre-sintered in an air atmosphere;
[0016] 7) Hot isostatic pressing sintering: The pre-sintered green body is subjected to hot isostatic pressing treatment; then planar grinding and polishing treatment are carried out to obtain the manganese (Mn 2+ ion)-doped aluminum-rich magnesium aluminate spinel transparent ceramic phosphor.
[0017] In the above solution, in the ball milling and mixing step of step 1), the mixing is carried out for 16-24 h, the rotation speed of the ball mill is 300-600 rpm, and the material-ball ratio is 1:4-5.
[0018] Furthermore, the ball milling step in step 1) adopts a wet milling process, and the ball milling medium used is composed of a liquid medium and grinding balls. The liquid medium can be selected from anhydrous ethanol, etc., and the grinding balls can be selected from alumina balls, etc.
[0019] Furthermore, the total amount of the liquid medium, grinding balls and raw materials accounts for 70-90% of the tank capacity.
[0020] In the above scheme, in step 1), the product is sieved through a 100-mesh sieve.
[0021] In the above scheme, the temperature used in the high temperature solid phase reaction in step 2) is 1200-1550°C, the insulation time is 1-4h, and the heating rate is 3-5°C / min.
[0022] In the above scheme, the ball milling step in step 2) adopts a wet milling process, the ball milling rate is 300-600rpm, the ball milling time is 36-48h, and the material-to-ball ratio is 1:4-5; the ball milling medium used includes a liquid medium and grinding balls, the liquid medium can be anhydrous ethanol, etc., and the grinding balls can be alumina balls, etc.
[0023] Furthermore, the Mg 1-x-y Al 2+2x / 3 The solid-liquid ratio of the O4:yMn single-phase compound to the liquid medium is 1g:2~4ml.
[0024] In the above scheme, in step 2), the product is sieved through a 100-mesh sieve.
[0025] In the above scheme, the dry pressing step adopts an axial unidirectional pressurization method with a pressure of 18 to 20 MPa and a pressure holding time of 2 to 4 minutes.
[0026] In the above scheme, the pressure used in the cold isostatic pressing treatment is 150-250 MPa, and the pressure holding time is 5-15 minutes.
[0027] In the above scheme, the pre-sintering step is to first heat the temperature to 1200-1300°C at a rate of 5-10°C / min in an air atmosphere, and then heat the temperature to 1500-1700°C at a rate of 3-5°C / min, and the holding time is 2-8h.
[0028] Furthermore, in the pre-sintering step, alumina powder is used to embed the green embryo.
[0029] In the above scheme, the temperature of the hot isostatic pressing treatment is 1750-1850°C, the pressure is 100-200 MPa, the atmosphere is an inert gas, the time is 1-10 hours, and the heating rate is 5-10°C / min.
[0030] Furthermore, the inert gas may be argon or the like.
[0031] In the above scheme, in the hot isostatic pressing step, the pre-sintered embryonic body is placed in a tungsten crucible.
[0032] In the above solution, the roughness of double-sided polishing of the plane grinding and polishing ceramic block can be at micron level or higher.
[0033] The manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor prepared according to the above scheme has a thickness of 2 to 8 mm, has green light emission, and a half-peak width of 33 to 37 nm. The transmittance of the 2 to 3 mm sample at 800 nm can reach more than 83%; the thermal conductivity is 8.6 to 12.4 W·m -1 ·K -1 Compared with room temperature, its luminous intensity is maintained at 86.8-88.6% at 150°C; the internal quantum efficiency can reach 80.1-96%, and the luminous efficiency of WLED package is 35-85lm / W.
[0034] The manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor is used to prepare a WLED device, which does not need to be coated on the surface of the blue light chip with an organic resin or a silicone resin, and can be directly fixed and packaged.
[0035] The principle of the present invention is:
[0036] The present invention firstly dissolves the activator Mn ions into the aluminum-rich spinel powder to prepare Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder, by changing the ball milling and sieving methods to optimize the uniformity and fluidity of the powder; then control the heating rate in the air, sinter to close the pores, and form a large amount of Mn 2+ With a small amount of Mn 4+ The coexistence of sintered bodies can reduce the sintering temperature and form fine grains; finally, hot isostatic pressing is carried out under higher temperature and inert atmosphere to further cause reduction reaction and realize Mn 2+ Solid solution, and use physical methods to isolate carbon pollution; at high temperature, ions will volatilize to form a small amount of gas, which can eliminate residual pores in the ceramic, remove dislocations, impurities, vacancies and other defects in the luminescent area, improve crystal quality and uniformity, increase light extraction rate, and obtain green light Mg with high quantum efficiency and narrow half-peak width. 1-x-y Al 2+2 / 3x O4:yMn fluorescent transparent ceramics.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1) The present invention prepares fluorescent transparent ceramics by a pressureless combined with hot isostatic pressing sintering method. By optimizing the process, the sintering temperature can be effectively reduced and the optical quality can be improved. For the first time, a preparation method for green fluorescent transparent ceramic block materials is proposed. The process involved is controllable, the technology is convenient and easy to regulate, and it can be flexibly applied to the sintering of samples of different compositions and sizes, which is easy to promote.
[0039] 2) The present invention changes the composition of the matrix in the fluorescent transparent ceramic so that the Mn 2+ The local structure of the ions changes, thereby adjusting the wavelength of the green light emission spectrum of the fluorescent transparent ceramic, realizing the regulation of the fluorescence performance, and obtaining a green light fluorescent transparent ceramic bulk material; it has the advantages of high optical quality, narrow half-peak width emission, high thermal stability and high thermal conductivity, and has a wide range of applicability;
[0040] 3) The fluorescent transparent ceramic block material obtained by the present invention can effectively replace the traditional method of encapsulating powder with organic glue, which helps to solve the problems of heat dissipation and light efficiency conversion, is expected to improve the stability of LED devices, and solve the problem of fluorescence performance degradation caused by aging of plastic sealing glue during the use of high-power white light LEDs, effectively expanding the application field of white light LEDs. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The XRD pattern of the ceramic powder obtained in step 1) of Example 1;
[0042] Figure 2 The apparent images of the transparent ceramics prepared in Examples 1 to 3 of the present invention, from left to right are Examples 1, 2, and 3;
[0043] Figure 3 This is a SEM microstructure image of the pre-fired ceramic obtained in step 2) of Example 1 of the present invention;
[0044] Figure 4 This is a SEM microstructure image of the transparent ceramic obtained in step 3) of Example 1 of the present invention;
[0045] Figure 5 is the linear transmittance of the transparent ceramic obtained in step 3) of Examples 1, 2, and 3 of the present invention;
[0046] Figure 6 The fluorescence spectrum of the transparent ceramic obtained in step 3) of Example 1;
[0047] Figure 7 Internal quantum efficiency test data of the transparent ceramic obtained in step 3) of Example 1 of the present invention.
[0048] Figure 8 Variable temperature fluorescence spectrum of the transparent ceramic obtained in step 3) of Example 1 of the present invention.
[0049] Fig. 9 The appearance diagram of the WLED device after the transparent ceramic obtained in step 3) of Example 1 of the present invention is packaged with a blue light LED chip and red phosphor. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] Example 1
[0052] A Mn 2+ The ion-doped aluminum-rich magnesium-aluminum spinel fluorescent transparent ceramics, the preparation method thereof comprises the following steps:
[0053] 1) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn ceramic blank: MgO, Al2O3, and MnCO3 powders were weighed according to the molar percentage of 0.855:1.04:0.02, and added to anhydrous ethanol, and ball milled for 24 hours (the ball mill speed was 300 rpm, and the material-ball ratio was 1:4). The obtained slurry was then fully dried to obtain a powder mixture. The powder was sieved through 100 mesh and loaded into a corundum crucible and placed in a muffle furnace. The powder was heated to 1400°C at a heating rate of 5°C / min for 2 hours to synthesize a single-phase stoichiometric MgO:0.02Mn ceramic blank. 0.855 Al 2.08 O4:0.02Mn ceramic powder; then Mg 0.855 Al 2.08 O4:0.02Mn powder was added to anhydrous ethanol and ball-milled for 48 hours (ball-milling speed was 300 rpm, material-ball ratio was 1:4), the obtained slurry was fully dried to obtain a single-phase powder, the powder was sieved through 100 mesh, 2 g of the powder was placed in a steel mold, an axial pressure of 18 MPa was applied (pressure was maintained for 2 to 3 minutes), and then a 200 MPa cold isostatic pressing treatment (pressure was maintained for 10 minutes) was performed to obtain a uniform ceramic blank;
[0054] 2) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn pre-sintered ceramics: The ceramic body was placed in a corundum crucible and placed in a high-temperature muffle furnace. It was heated to 1300°C at a heating rate of 10°C / min in an air atmosphere, and then heated to 1600°C at a heating rate of 3°C / min. The temperature was kept for 6 hours to obtain MgO4:0.02Mn pre-sintered ceramics. 0.855 Al 2.08 O4: 0.02Mn pre-fired ceramic;
[0055] 3) Mg 0.855 Al2.08 O4:0.02Mn 2+ Preparation of transparent ceramics: The ceramic sintered body obtained in step 2) was subjected to hot isostatic pressing at a temperature of 1800°C, a heating rate of 10°C / min, a pressure of 180 MPa, and a holding time of 5 h to obtain a single-phase Mg 0.855 Al 2.08 O4:0.02Mn 2+ Transparent ceramic sample (transparent ceramic phosphor).
[0056] After grinding and polishing, the transmittance of the 2mm thick sample at 800nm was 83.75%, and the average grain size was 10μm. The internal quantum efficiency of the phosphor under 449nm blue light excitation was 96%, the half-peak width was 33nm, and its luminous intensity remained at 88.6% of that at room temperature at 150℃. The thermal conductivity of the phosphor was 12.4W·m -1 ·K -1 .
[0057] The obtained transparent ceramic phosphor and red luminescent phosphor K2SiF6:Mn 4+ The blue InGaN chip is packaged as follows: the red phosphor K2SiF6:Mn 4+ Mixed with UV curing adhesive (Leaftop 6300) at a mass ratio of 1:1, it is applied on the blue InGaN chip, and then the fluorescent transparent ceramic is placed directly on the chip and fixed with UV curing adhesive (Leaftop 6300). The luminous efficiency of the packaged WLED is 37lm / w, and the color gamut is 126% of the value of the National Television Standards Committee.
[0058] Example 2
[0059] A Mn 2+ The ion-doped aluminum-rich magnesium-aluminum spinel fluorescent transparent ceramics, the preparation method thereof comprises the following steps:
[0060] 1) Mg 0.73 Al 2.16 Preparation of O4:0.02Mn ceramic blank: MgO, Al2O3, and MnCO3 powders were weighed according to the molar percentage of 0.73:1.08:0.02, and added to anhydrous ethanol, and ball milled for 24 hours (the ball mill speed was 300 rpm, and the material-ball ratio was 1:4). The obtained slurry was then fully dried to obtain a powder mixture. The powder was sieved through 100 mesh and loaded into a corundum crucible and placed in a muffle furnace. The powder was heated to 1550°C at a heating rate of 5°C / min for 2 hours to synthesize a single-phase stoichiometric MgO:0.02Mn ceramic blank. 0.73 Al 2.16 O4:0.02Mn ceramic powder; then Mg 0.73Al 2.16 O4:0.02Mn powder was added to anhydrous ethanol and ball-milled for 48 hours (ball-milling speed was 300 rpm, material-ball ratio was 1:4), the obtained slurry was fully dried to obtain a single-phase powder, the powder was sieved through 100 mesh, 2 g of the powder was placed in a steel mold, an axial pressure of 18 MPa was applied (pressure was maintained for 2 to 3 minutes), and then a 200 MPa cold isostatic pressing treatment (pressure was maintained for 10 minutes) was performed to obtain a uniform ceramic green body;
[0061] 2) Mg 0.73 Al 2.16 Preparation of O4:0.02Mn pre-sintered ceramics: The ceramic body was placed in a corundum crucible and placed in a high-temperature muffle furnace. It was heated to 1300°C at a heating rate of 10°C / min in an air atmosphere, and then heated to 1650°C at a heating rate of 3°C / min. The temperature was kept for 6 hours to obtain MgO4:0.02Mn pre-sintered ceramics. 0.73 Al 2.16 O4: 0.02Mn pre-fired ceramic;
[0062] 3) Mg 0.73 Al 2.16 O4:0.02Mn 2+ Preparation of transparent ceramics: The ceramic sintered body obtained in step 2 was subjected to hot isostatic pressing at a temperature of 1800°C, a heating rate of 10°C / min, a pressure of 180 MPa, and a holding time of 5 h to obtain a single-phase Mg 0.73 Al 2.16 O4:0.02Mn 2+ Transparent ceramic samples.
[0063] After grinding and polishing, the transmittance of the 2mm thick sample at 800nm is 83.63%, and the average grain size is 9.4μm. The internal quantum efficiency of the phosphor under 448nm blue light excitation is 86%, the half-peak width is 34nm, and its luminous intensity remains 87.5% of that at room temperature at 150℃. The thermal conductivity of the phosphor is 11.2W·m -1 ·K -1 .
[0064] The luminous efficiency of the WLED packaged according to the method described in Example 1 is 35 lm / w, and the color gamut is 116% of the value of the National Television Standards Committee.
[0065] Example 3
[0066] A Mn 2+ The ion-doped aluminum-rich magnesium-aluminum spinel fluorescent transparent ceramics, the preparation method thereof comprises the following steps:
[0067] 1) Mg 0.70 Al 2.16Preparation of O4:0.05Mn ceramic blank: MgO, Al2O3, and MnCO3 powders were weighed according to the molar percentage of 0.70:1.08:0.05, and added to anhydrous ethanol, and ball milled for 24 hours (the ball mill speed was 300 rpm, and the material-ball ratio was 1:4). The obtained slurry was then fully dried to obtain a powder mixture. The powder was sieved through 100 mesh and loaded into a corundum crucible and placed in a muffle furnace. The powder was heated to 1550°C at a heating rate of 5°C / min for 2 hours to synthesize a single-phase stoichiometric MgO:0.05Mn ceramic blank. 0.70 Al 2.16 O4:0.05Mn ceramic powder; then Mg 0.70 Al 2.16 O4:0.05Mn powder was added to anhydrous ethanol and ball milled for 48h (the ball mill speed was 300rpm, and the material-ball ratio was 1:4). The obtained slurry was fully dried to obtain a single-phase powder. After the powder was sieved through 100 mesh, 2g of the powder was placed in a steel mold and an axial pressure of 18MPa was applied (maintaining pressure for 2-3min). Then, a cold isostatic pressing treatment of 200MPa was performed (maintaining pressure for 10min) to obtain a uniform ceramic green body.
[0068] 2) Mg 0.70 Al 2.16 Preparation of O4:0.05Mn pre-sintered ceramics: The ceramic body was placed in a corundum crucible and placed in a high-temperature muffle furnace. It was heated to 1300°C at a heating rate of 10°C / min in an air atmosphere, and then heated to 1625°C at a heating rate of 3°C / min. The temperature was kept for 2 h to obtain MgO4:0.05Mn pre-sintered ceramics. 0.70 Al 2.16 O4:0.05Mn pre-fired ceramic;
[0069] 3) Mg 0.70 Al 2.16 O4:0.05Mn 2+ Preparation of transparent ceramics: The ceramic sintered body obtained in step 2 was subjected to hot isostatic pressing at a temperature of 1800°C, a heating rate of 10°C / min, a pressure of 180 MPa, and a holding time of 5 h to obtain a single-phase Mg 0.70 Al 2.16 O4:0.5Mn 2+ Transparent ceramic samples.
[0070] After grinding and polishing, the transmittance of the 2mm thick sample at 800nm is 84.64%, and the average grain size is 13.2μm. The internal quantum efficiency of the phosphor under 448nm blue light excitation is 80.1%, the half-peak width is 37nm, and its luminous intensity remains 86.8% of that at room temperature at 150℃. The thermal conductivity of the phosphor is 8.6W·m -1 ·K -1 .
[0071] The luminous efficiency of the WLED packaged according to the method described in Example 1 is 85 lm / w, and the color gamut is 112% of the value of the National Television Standards Committee.
[0072] Example 4
[0073] A Mn 2+ The ion-doped aluminum-rich magnesium-aluminum spinel fluorescent transparent ceramics, the preparation method thereof comprises the following steps:
[0074] 1) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn ceramic blank: MgO, Al2O3, and MnCO3 powders were weighed according to the molar percentage of 0.855:1.04:0.02, and added to anhydrous ethanol, and ball milled for 24 hours (the ball mill speed was 300 rpm, and the material-ball ratio was 1:4). The obtained slurry was then fully dried to obtain a powder mixture. The powder was sieved through 100 mesh and loaded into a corundum crucible and placed in a muffle furnace. The powder was heated to 1400°C at a heating rate of 5°C / min for 2 hours to synthesize a single-phase stoichiometric MgO:0.02Mn ceramic blank. 0.855 Al 2.08 O4:0.02Mn ceramic powder; then Mg 0.855 Al 2.08 O4:0.02Mn powder was added to anhydrous ethanol and ball-milled for 48 hours (ball-milling speed was 300 rpm, material-ball ratio was 1:4), the obtained slurry was fully dried to obtain a single-phase powder, the powder was sieved through 100 mesh, 8 g of the powder was placed in a steel mold, an axial pressure of 20 MPa was applied (pressure was maintained for 3 minutes), and then a 200 MPa cold isostatic pressing treatment (pressure was maintained for 10 minutes) was performed to obtain a uniform ceramic blank;
[0075] 2) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn pre-sintered ceramics: The ceramic body was placed in a corundum crucible and placed in a high-temperature muffle furnace. It was heated to 1300°C at a heating rate of 10°C / min in an air atmosphere, and then heated to 1625°C at a heating rate of 3°C / min. The temperature was kept for 6 hours to obtain MgO4:0.02Mn pre-sintered ceramics. 0.855 Al 2.08 O4: 0.02Mn pre-fired ceramic;
[0076] 3) Mg 0.855 Al 2.08 O4:0.02Mn 2+ Preparation of transparent ceramics: The ceramic sintered body obtained in step 2) was subjected to hot isostatic pressing at a temperature of 1800°C, a heating rate of 10°C / min, a pressure of 180 MPa, and a holding time of 5 h to obtain a single-phase Mg 0.855 Al 2.08O4:0.02Mn 2+ Transparent ceramic samples.
[0077] After grinding and polishing, the 8mm thick sample has a transmittance of 78% at 800nm and an average grain size of 15μm. The internal quantum efficiency of the phosphor under 449nm blue light excitation is 73% and the half-peak width is 33nm.
[0078] Mg obtained in step 1) of Example 1 0.855 Al 2.08 The XRD pattern of O4:0.02Mn powder is shown in Figure 1 The Bragg angle of the diffraction peak of the powder is consistent with the pure spinel crystal structure, and no impurity phase is observed. The fluorescent transparent ceramic sample obtained in step 3) of Examples 1, 2, and 3 is shown in FIG. Figure 2 , the color is green, and the text on the back is clearly visible.
[0079] The SEM microstructures of the pre-fired ceramic obtained in step 2) and the transparent ceramic obtained in step 3) after surface etching in Example 1 are shown as follows: Figure 3 and Figure 4 The pre-fired ceramics obtained in step 2) are all grain boundary pores, with almost no intracrystalline pores; the transparent ceramic sample obtained in step 3) has a microstructure with clear grain boundaries and no pores, indicating that the relative density of the sample is extremely high and the average grain size is only about 10 μm.
[0080] The transmittance spectrum of the transparent ceramic obtained in step 3) of Examples 1, 2 and 3 is shown in Figure 5 , it can be seen that the obtained sample has extremely high transmittance in the visible light range.
[0081] The fluorescence spectrum of the transparent ceramic obtained in step 3) of Example 1 is shown in Figure 6 , the luminescent color is green and the emission wavelength is 520nm.
[0082] The internal quantum efficiency measurement data of the transparent ceramic obtained in step 3) of Example 1 is shown in Figure 7 .
[0083] The emission spectrum of the transparent ceramic obtained in step 3) of Example 1 in the temperature range of 298 to 500 K is shown in FIG. Figure 8 , it can be seen that it has good thermal stability of luminescence.
[0084] The transparent ceramic obtained in step 3) of Example 1 is used to prepare a WLED device with a blue LED chip and a red phosphor. The specific steps include: using a blue InGaN chip, a fluorescent transparent ceramic and a commercially available red luminescent phosphor K2SiF6:Mn 4+The encapsulation method is to mix the powder with UV curing adhesive in a 1:1 mass ratio and then apply it on the chip. The fluorescent transparent ceramic is a disc, so it can be placed directly on the chip and then fixed with UV curing adhesive. The encapsulated WLED device is shown in Fig. 9 .
[0085] The fluorescent transparent ceramic block material obtained by the present invention can effectively replace the traditional method of encapsulating powder with organic glue, help solve the problems of heat dissipation and light efficiency conversion, and is expected to improve the stability of LED devices and solve the problem of fluorescence performance degradation of high-power white light LEDs due to aging of plastic sealing glue during use.
[0086] Comparative Example 1
[0087] A Mn 2+ The ion-doped aluminum-rich magnesium-aluminum spinel fluorescent transparent ceramics, the preparation method thereof comprises the following steps:
[0088] 1) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn ceramic blank: MgO, Al2O3, and MnCO3 powders were weighed according to the molar percentage of 0.855:1.04:0.02, and added to anhydrous ethanol, and ball milled for 24 hours (the ball mill speed was 300 rpm, and the material-ball ratio was 1:4). The obtained slurry was then fully dried to obtain a powder mixture. The powder was sieved through 100 mesh and loaded into a corundum crucible and placed in a muffle furnace. The powder was heated to 1400°C at a heating rate of 5°C / min for 2 hours to synthesize a single-phase stoichiometric MgO:0.02Mn ceramic blank. 0.855 Al 2.08 O4:0.02Mn ceramic powder; firstly, the synthesized Mg 0.855 Al 2.08 O4:0.02Mn powder was directly dry-milled for 12 hours (ball milling rate of 300, material-to-ball ratio of 1:4), then added to anhydrous ethanol for wet milling for 24 hours (ball milling rate of 300rpm, material-to-ball ratio of 1:4), the obtained slurry was fully dried to obtain a single-phase powder, the powder was sieved through 200 mesh, 2g of powder was placed in a steel mold, an axial pressure of 18MPa was applied (pressure maintenance for 2-3min), and then a 200MPa cold isostatic pressing treatment (pressure maintenance for 10min) was performed to obtain a uniform ceramic green body;
[0089] 2) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn pre-sintered ceramics: The ceramic body was placed in a corundum crucible and placed in a high-temperature muffle furnace. It was heated to 1300°C at a heating rate of 10°C / min in an air atmosphere, and then heated to 1600°C at a heating rate of 3°C / min. The temperature was kept for 6 hours to obtain MgO4:0.02Mn pre-sintered ceramics. 0.855 Al2.08 O4: 0.02Mn pre-fired ceramic;
[0090] 3) Mg 0.855 Al 2.08 O4:0.02Mn 2+ Preparation of transparent ceramics: The ceramic sintered body obtained in step 2) was subjected to hot isostatic pressing at a temperature of 1800°C, a heating rate of 10°C / min, a pressure of 180 MPa, and a holding time of 5 h to obtain a single-phase Mg 0.855 Al 2.08 O4:0.02Mn 2+ Transparent ceramic samples.
[0091] After grinding and polishing, the transmittance of the 2mm thick sample at 800nm is 78.3%, the average grain size is 22μm. The internal quantum efficiency of the phosphor under 448nm blue light excitation is 68%.
[0092] Comparative Example 2
[0093] A Mn 2+ The ion-doped aluminum-rich magnesium-aluminum spinel fluorescent transparent ceramics, the preparation method thereof comprises the following steps:
[0094] 1) Mg 0.855 Al 2.08 Preparation of O4:0.02Mn ceramic blank: MgO, Al2O3, and MnCO3 powders were weighed according to the molar percentage of 0.855:1.04:0.02, and added to anhydrous ethanol, and ball milled for 24 hours (the ball mill speed was 300 rpm, and the material-ball ratio was 1:4). The obtained slurry was then fully dried to obtain a powder mixture. The powder was sieved through 100 mesh and loaded into a corundum crucible and placed in a muffle furnace. The powder was heated to 1400°C at a heating rate of 5°C / min for 2 hours to synthesize a single-phase stoichiometric MgO:0.02Mn ceramic blank. 0.855 Al 2.08 O4:0.02Mn ceramic powder; firstly, the synthesized Mg 0.855 Al 2.08 O4:0.02Mn powder was added to anhydrous ethanol for wet grinding and ball milling for 48h (ball milling rate was 300rpm, material-ball ratio was 1:4), the obtained slurry was fully dried to obtain a single-phase powder, the powder was sieved through 100 mesh, 2g of powder was placed in a steel mold, an axial pressure of 18MPa was applied (pressure was maintained for 2-3min), and then a 200MPa cold isostatic pressing treatment (pressure was maintained for 10min) was performed to obtain a uniform ceramic green body;
[0095] 2) Mg 0.855 Al 2.08Preparation of O4:0.02Mn pre-sintered ceramics: The ceramic body was placed in a corundum crucible and placed in a high-temperature muffle furnace. It was heated to 1600°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 hours to obtain MgO4:0.02Mn pre-sintered ceramics. 0.855 Al 2.08 O4: 0.02Mn pre-fired ceramic;
[0096] 3) Mg 0.855 Al 2.08 O4:0.02Mn 2+ Preparation of transparent ceramics: The ceramic sintered body obtained in step 2) was subjected to hot isostatic pressing at a temperature of 1800°C, a heating rate of 10°C / min, a pressure of 180 MPa, and a holding time of 5 h to obtain a single-phase Mg 0.855 Al 2.08 O4:0.02Mn 2+ Transparent ceramic samples.
[0097] After grinding and polishing, the transmittance of the 2mm thick sample at 800nm is 70.3%, the average grain size is 40μm. The internal quantum efficiency of the phosphor under 448nm blue light excitation is 38%.
[0098] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor, characterized in that: It is a single-phase magnesium-aluminum spinel structure with a stoichiometric formula of Mg 1-x-y Al 2+2x / 3 O4:yMn, where 0 <x≤0.25,0.004≤y≤0.1。 2. The manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor according to claim 1, characterized in that: It has a block structure with a thickness of 2 to 8 mm.
3. The manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor according to claim 1, characterized in that: It has green fluorescence and an internal quantum efficiency of over 73%.
4. The method for preparing the manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor according to claim 1, characterized in that: The steps include: firstly, preparing Mg by high temperature solid phase reaction 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder, the prepared powder is ball-milled, dried and sieved in sequence; the sieved powder is then dry-pressed and pressurelessly sintered to obtain a ceramic sintered body, and the ceramic sintered body is then hot isostatically pressed.
5. The preparation method according to claim 4, characterized in that: The Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder is prepared as follows: Using MgO, Al2O3, and MnCO3 as raw materials, proportion them according to the molar ratio of 1-x-y:(1+x / 3):y, where 0<x≤0.25; 0.004≤x≤0.1; ball mill and mix, then sieve; conduct high-temperature solid-state reaction on the mixed powder obtained by sieving to obtain Mg 1-x-y Al 2+2x / 3 O4:yMn compound, ball mill it, and sieve to obtain Mg 1-x-y Al 2+2x / 3 O4:yMn single-phase ceramic powder.
6. The preparation method according to claim 5, characterized in that: The ball milling, drying and sieving steps include: adopting a wet milling process, with a ball milling rate of 300-600 rpm, a material-ball ratio of 1:4-5, and a time of 36-48 hours; fully drying the obtained slurry to obtain a single-phase powder, and sieving the powder to 100 meshes.
7. The preparation method according to claim 4, characterized in that: The dry pressing step comprises: dry pressing the powder to obtain a green embryo, and then performing a cold isostatic pressing process.
8. The preparation method according to claim 4, characterized in that: The pre-sintering step comprises: in an air atmosphere, firstly heating to 1200-1300° C. at a speed of 5-10° C. / min, then heating to 1500-1700° C. at a speed of 3-5° C. / min, and keeping the temperature for 2-8 hours.
9. The preparation method according to claim 4, characterized in that: The hot isostatic pressing treatment is carried out at a temperature of 1750-1850° C., a pressure of 100-200 MPa, an inert gas atmosphere, and a time of 1-10 hours.
10. Use of the manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor according to any one of claims 1 to 3 or the manganese-doped aluminum-rich magnesium-aluminum spinel transparent ceramic phosphor obtained by the preparation method according to any one of claims 4 to 9 in preparing white light emitting diodes.